Does a theory of action approach help teachers engage in evidence-informed self-improvement?. (1st July 2018) - Flood, Jane; Brown, Chris
Abstract : This article reports on how using Theories of Action (TofA) can help teachers scale up evidence-informed teaching practices by aiding their understanding of why such interventions have been effective and which aspects are key to driving change. This paper reports on a specific approach: a partnership between an academic and three schools. The findings based on interviews with 15 teachers and school leaders (the whole of the federation's teaching staff), and pre- and post-intervention surveys (undertaken with 13 staff members) suggests that the scale-up of evidence-informed practice, when aided by TofAs, can lead to substantial impact on teacher and pupil outcomes. The paper concludes that the effective scale-up of evidence-informed interventions is grounded in teachers' understanding of why interventions have been successful and how that success might be realized in a new context. Correspondingly, when teachers are shown how to use TofAs to tailor interventions, this helps them ascertain how such interventions can be realized most effectively in their own settings.